The effect of Internet use on males' body mass index and overweight: Evidence from China - Weigang Liu; Jian Liu; Jens-Peter Loy; Yanjun Ren (Journal of Men's Health, 2023)
The effects of increasing Internet use in developing economies have attracted various attention from politicians and academic researchers, while the literature investigating the effects of Internet use on nutrition and health is insufficient. In particular, research on China, with its large overweight population, is still not clear and complete. This study aims to evaluate the effect of Internet use on body mass index (BMI) and overweight for males in China and shed light on the underlying mechanisms of the effect. To address the non-random distribution problem of Internet use and control for unobservable factors that might bias the estimates we are interested in, an endogenous switching regression model is applied, an econometric method in which counterfactual analysis is used to obtain the average treatment effect of Internet use on BMI and overweight. The study sample is chosen from longitudinal research data from the China Health and Nutrition Survey, with 12,846 observations covering 5 waves. Estimation results indicate that Internet use could reduce BMI and the probability of being overweight by 3.626% and 33.963%, respectively. Heterogeneity analysis shows that Internet use has a greater effect on males living in urban areas and those with higher education. We also reveal that reducing total energy intake and macronutrient intake and increasing dietary knowledge levels and the time spent on exercising serve as important mechanisms through which Internet use can have an effect on BMI and overweight. This study shows that Internet use has a beneficial effect on BMI and overweight of males in China. Therefore, internet platforms may be an effective way to regulate males' macronutrient intake and BMI and overweight. More importantly, using Internet platforms to circulate information about healthy diets may contribute to improving dietary knowledge and the prevalence of overweight.
Keywords: 300; Internet use; males; BMI; overweight; macronutrient intake